Neurological mechanism and efficacy of acupuncture for breast cancer-related insomnia: a study protocol for randomized clinical trial - Lumin Liu; Ping Yin; Yiyue Dong; Qian Fan; Yisheng Huai; Shijie Zhang; Shunyi Lv; Xueyang Wang; Yuelai Chen (Frontiers in Neurology, 2023)
BackgroundBreast cancer survivors (BCSs) are at a higher risk of developing insomnia. The negative effects of cancer-related insomnia (CRI) include depression, anxiety, fatigue, aggressive pain, impaired immune functioning, decreased quality of life, and even increased cancer mortality. Although preliminary progress has been made in the treatment of CRI with acupuncture, the evidence is insufficient and the neurological mechanism underlying the effect of acupuncture is still unclear.MethodsThe study employs a single-blinded, randomized, controlled trial design. A total of 80 participants will be randomly allocated in a 1:1 ratio to either the treatment group (n = 40) or the control group (n = 40). The former will receive acupuncture treatment, while the latter will receive sham acupuncture treatment. Both groups will receive 12 sessions over a 4-week period, three times per week (every other day), and each session will last for 30 min. Follow-up assessments will be conducted in week 8. The primary outcome will be the treatment response rate. Secondary outcomes include the change in Insomnia Severity Index (ISI), the treatment remission rate, actigraphy sleep assessment, Generalized Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Quality of Life Core Scale (QLQ-C30), the weekly usage of remedial drugs, and functional magnetic resonance imaging (fMRI) analysis. Data for the outcomes will be collected at week 0 (the baseline), week 1 (the intervention period), week 4 (the post-treatment period), and week 8 (the follow-up period).DiscussionThe objective of this study is to assess the efficacy of acupuncture for patients with CRI in comparison with sham acupuncture. Additionally, the research aims to explore the neuropathological mechanisms of CRI and provide the first evidence on the characteristics of acupuncture treatment using fMRI. We expect that the results of this study will provide valuable scientific evidence of acupuncture treatment for CRI.Clinical trial registration: Chinese Clinical Trial Registry, identifier ChiCTR2300070349: https://www.chictr.org.cn/showproj.html?proj=188677.